Behaviour of impact- and vibratory-driven piles in stiff clay during installation and static loading (Journal of Nepal Geological Society, 2006)
This paper summarises the results of an extensive field test carried out in the framework of the "French National Research Project on Vibratory Driving" and the ProfilArbed Research Programme, to investigate and compare the behaviour and performance of eight impact- and vibratory-driven piles. The test site is located in Northern France. The subsoil consists of dense Flanders clay. The piles were driven using an ICE8 l5 vibrator and an IHC70s impact hammer to the same depth. All these piles were instrumented with accelerometers and strain gauges positioned at the top and bottom of the piles. Penetration rate, uplift load applied by the crane, vibration transmitted to the ground, operating pressure, oil flow at the vibratory power-pack, and energy per blow for the hammer were continuously recorded. The paper presents the main results obtained from double sheet piles (AUl6 type) driven to 7 m depth, a small wall of two double sheet piles (AU20 type) driven to 8 m depth, HP bearing piles driven to 10.2 m, and steel open-ended tubes of508 mm diameter driven to 9.4 m depth. After a delay of 6 to 8 weeks, the piles were statically loaded to failure. The piles were instrumented with removable extensometers, which made it possible to measure the mobilisation of shaft friction and toe resistance. The measured bearing capacity was significantly lower for the vibratory-driven piles (around 35%) and it is consistent with the results obtained by the Laboratoire des Ponts et Chaussees de Paris at other sites.